Serum total oxidant and antioxidant status in earthquake survivors with post-traumatic stress disorder - (:unkn) unknown (CAMBRIDGE UNIV PRESS, 2015)
Objective Oxidative stress has been shown to play an important role in the pathogenesis of post-traumatic stress disorder (PTSD). Although there are some studies on oxidative stress and PTSD, there is no report available on the serum total oxidant and antioxidant status in earthquake survivors with PTSD. Therefore, this study aimed to investigate the serum total oxidant and antioxidant status in earthquake survivors with chronic PTSD. Material and Methods The study group included 45 earthquake survivors with PTSD and 40 earthquake survivors without PTSD. The oxidative status was determined using the total antioxidant status and total oxidant status (TOS) measurements and by calculating the oxidative stress index (OSI). Results There were no statistically significant differences in the total antioxidant status, TOS, or OSI when comparing individuals with and without PTSD (all, p>0.05). There were no correlations between Clinician-Administered PTSD Scale scores and oxidant and antioxidant stress markers (all, p>0.05). Conclusions Our results suggest that the total oxidant and antioxidant status may not affect earthquake survivors with PTSD. This is the first study to evaluate the oxidative status in earthquake survivors with PTSD. Further studies are necessary to confirm these findings.
Keywords: earthquake survivors; oxidative stress index; post-traumatic stress disorder; total antioxidant status; total oxidant status; OXIDATIVE STRESS; LIPID-PEROXIDATION; NITRIC-OXIDE; DEPRESSION; ANXIETY; DAMAGE; PTSD